Developing communicative and interpersonal competences through research-based projects: a student-centred approach - Simões, Anabela (2021)
Presently, conducting research is a very relevant skill in academic and business-related contexts (Hunter et al., 2007). With this work, based on the idea that student-centred learning environments are likely to be more effective and conducive to a greater level of development of technical and interpersonal skills (Severiens et al., 2015), we aim at a) describing two project-works proposed to 2nd year Office Management and Business Communication (OMBC) students that seek to integrate knowing and doing while developing students’ research and interpersonal skills, and b) presenting students’ perception of the activities. The collected data indicates that both technical and interpersonal competencies were successfully addressed.